Analisis Penerapan Subject Specific Pedagogy (SSP) Pembelajaran Ilmu Pengetahuan Alam dan Sosial pada Kurikulum Merdeka di Sekolah Dasar Negeri 156/VI Durian Betakuk - Padilah Padilah; Ahmad Sayuti Nainggolan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
One of the pedagogical approaches that supports the achievement of educational goals is Subject Specific Pedagogy (SSP). In science and social studies subjects, the application of SSP is particularly important because both subjects are closely related to everyday life. This study aims to analyze in depth how Subject Specific Pedagogy is implemented in science and social studies learning at SD Negeri 156/VI Durian Betakuk.This research employs a qualitative descriptive strategy, a method used by researchers to discover data or theories related to the study within a specific period. Based on interviews with the principal and teachers at SDN 156/VI Durian Betakuk, it can be concluded that the implementation of SSP in the learning of IPAS (Integrated Science and Social Studies) within the Merdeka Curriculum still faces various challenges, but also presents opportunities for improving the quality of education.The main challenges lie in the lack of comprehensive understanding of SSP among teachers, limited availability of teaching modules that are relevant to local contexts, and the unfamiliarity of teachers in independently developing and adapting teaching materials. However, based on the results of the research conducted at SD Negeri 156/VI Durian Betakuk, it can be concluded that the implementation of SSP in IPAS learning within the Merdeka Curriculum has been fairly effective and has had a positive impact on the learning process.Teachers have demonstrated a good understanding of the SSP concept and are able to adapt learning strategies to the characteristics of students and their surrounding environment. Teaching materials are delivered contextually, connected to students' real-life experiences, making them easier to understand and increasing students' learning motivation.